Subglacial hydrology of the Fennoscandian and Barents Sea ice sheets - Shackleton, Calvin (Quaternary Science Reviews, 2019)
The drainage of meltwater beneath ice sheets exerts a fundamental control on ice flow variability, by regulating the lubrication of the ice-bed interface, and determining subglacial sediment shear strengths. This thesis investigates meltwater drainage of the Fennoscandian and Barents Sea ice sheets through the combined application of geomorphologically based reconstruction and modelling of subglacial hydraulic pressure potential. Meltwater processes at a wide range of spatial and temporal scales are studied, from drainage patterns at the ice sheet scale over an entire glaciation, to more focussed studies of meltwater and its impacts on ice dynamic behaviour at the ice sheet interior and margins. Hydraulic potential modelling reveals meltwater drainage routes and potential sites for water storage within palaeo-subglacial lakes over the Barents Sea and Fennoscandia. Also, migration paths of ice marginal drainage outlets are predicted throughout deglaciation, highlighting regions of focussed sediment and freshwater delivery to the ice margins. Geomorphological reconstructions reveal iceberg calving characteristics and meltwater dominated deposition at a retreating ice margin south of Svalbard and in the central Barents Sea, glacial and meltwater landforms document highly dynamic drainage systems operating at various stages of ice development. During ice maximum conditions large meltwater conduits supplied water to the beds of downstream ice streams, and evidence for upstream subglacial lakes indicates the potential for cyclic filling and draining, regulating meltwater supply and modulating local and regional ice dynamics. During the later stages of deglaciation when ice was retreating through the central Barents Sea, esker ridges indicate conduits incised into overlying ice, and their morphology and spatial distribution suggests that supraglacial water sources may have connected to the bed and fed basal drainage systems.